Introduction - Mary Gobbi (Universidad de Deusto, 2020)
This edition of the Journal shows how different strategies - whether at the macro or micro level - are employed by Higher Education Institutions to address the 'soft' or 'employment' skills and experiences that prepare (post) graduates entering the labour market. While it is expected that graduates have acquired the necessary subject specific and generic competences associated with their field of study, these papers discuss how it is increasingly important that graduates can make positive transitions into the different dimensions of the employment market: be it at local or global level. Published online: 19 May 2020